Ответ:
1)4(3-x)+5x = 3(2x+4)
12-4х+5х = 6х+12
12-12 = 6х+4х-5х
0 = 5х
<u>х = 0.</u>
2)6(3x-5)-2x = 2(3-x)
18х-30<u>-2х</u> = 6<u>-2х</u>
18х = 6+30 = 36
<u>х = 2.</u>
Х+Х-24+Х+46=180
3Х=158
Х=51 2/3
Х+46=97 2/3
Х-22=29 2/3
Пошаговое объяснение:
х+5/12-9/20=11/15
х=11/15-5/12+9/20
приводим правую часть к общему знаменателю 60
х=44/60-25/60+27/60
х=(44-25+27)/60
х=46/60
х=23/30
Y=x²+14x+73 (0;0) L=?
y`=2x+14=0
2x+14=0 |÷2
x=-7
y=(-7)²+14*(-7)+73=49-98+73=24 ⇒ (-7;24)
L=√((-7-0)²+(24-0)²)=√(49+576)=√625=25.
Ответ: L=25.
39:3=13 Коля нарисовал
13+7=20 Вася нарисовал
13-7=6 Петя нарисовал